Effects of Extended Underwater Sections on the Physiological and Biomechanical Parameters of Competitive Swimmers - Veiga, Santiago; Pla, Robin; Qiu, Xiao; Boudet, David; Guimard, Alexandre (Frontiers in Physiology, 2022)
Despite changes in the underwater sections of swimming races affecting overall performance, there is no information about the effects of the apnea-induced changes on the physiological state of competitive swimmers. The aim of the present research was to examine the effect of changes in the underwater race sections on the physiological (blood lactate concentration, heart rate and rating of perceived exertion (RPE)) and biomechanical (underwater time, distance and velocity) parameters of competitive swimmers. Twelve youth competitive swimmers belonging to the national team (706 ± 28.9 FINA points) performed 2 x 75m efforts under three different conditions while maintaining a 200 m race pace: 1) free underwater sections, 2) kick number of condition 1 plus two kicks, and 3) maximum distance underwater. Overall performance was maintained, and underwater section durations increased from condition 1 to 3 as expected according to the experimental design. Heart rate and blood lactate concentration values did not show differences between conditions, but the RPE values were significantly greater (F2, 36 = 18.00, p = 0.001, η²: 0.50) for the constrained (conditions 2 and 3) versus the free underwater condition. Underwater parameters were modified within the 75 m efforts (lap 1 to lap 3), but the magnitude of changes did not depend on the experimental condition (all lap x condition effects p > 0.05). Controlled increases of underwater sections in trained swimmers can led to optimizing performance in these race segments despite small increases of perceived discomfort.